2010
DOI: 10.1186/1476-9255-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce apoptosis in human eosinophils and neutrophils

Abstract: BackgroundGranulocytes are important in the pathogenesis of several inflammatory diseases. Apoptosis is pivotal in the resolution of inflammation. Apoptosis in malignant cells is induced by histone deacetylase (HDAC) inhibitors, whereas HDAC inhibitors do not usually induce apoptosis in non-malignant cells. The aim of the present study was to explore the effects of HDAC inhibitors on apoptosis in human eosinophils and neutrophils.MethodsApoptosis was assessed by relative DNA fragmentation assay, annexin-V bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…Numerous studies have shown that HDACi can promote the production of IL-5, which is a lifesupporting cytokine for eosinophils (Donnelly et al 2004). It has been suggested that the mechanism of HDACi effect on eosinophilia is induction of granulocyte apoptosis (Kankaanranta et al 2010). Recent experiments have shown that HDACi could induce apoptosis in human eosinophils and neutrophils in the absence and presence of survival-prolonging cytokines and glucocorticoids.…”
Section: S a L I N E O V A -V E H O V A -T Smentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that HDACi can promote the production of IL-5, which is a lifesupporting cytokine for eosinophils (Donnelly et al 2004). It has been suggested that the mechanism of HDACi effect on eosinophilia is induction of granulocyte apoptosis (Kankaanranta et al 2010). Recent experiments have shown that HDACi could induce apoptosis in human eosinophils and neutrophils in the absence and presence of survival-prolonging cytokines and glucocorticoids.…”
Section: S a L I N E O V A -V E H O V A -T Smentioning
confidence: 99%
“…The activated GR could interact with specific transcription factors such as AP-1 and NF-jB and thus prevent the transcription of targeted inflammation genes. HDACi-induced loss of HDAC2 disrupts the association between GR and NF-jB (Kankaanranta et al 2010). In addition, in one study TSA was shown to enhance lipopolysaccharide-stimulated IL-8 and block attenuation of IL-8 transcription (Adcock et al 2007).…”
Section: S a L I N E O V A -V E H O V A -T Smentioning
confidence: 99%
“…Several studies show that HDACi modulate the acetylation of STAT1 and its transcriptional activity [30, 31]. The treatment of cells with HDACi alters protein degradation, signaling, gene expression, and apoptosis [32-34]. Accordingly, HDACi also are potent apoptosis inducers in certain cell types [28].…”
Section: Introductionmentioning
confidence: 99%
“…First, HDACi may induce the apoptosis of cytokine-producing inflammatory cells,56 57 though there are relatively few data as yet for this mechanism of action using normal rather than transformed cells. Second, HDACi may disrupt the functional microtubule network in monocytes and thereby disrupt exocytotic release of cytokines from lysosomes 58.…”
Section: Mechanisms Of Action and Caveatsmentioning
confidence: 99%